14C Mean residence time of soil organic carbon under contrasting climates in some of rangelands of Khozestan province, Iran - A. Owji; A. Landi; M. Khodadadi; S. Hojati (مجله علوم و فنون هسته‌ای, 2020)
Nowadays, to mitigate global warming, soil can play a significant role as a pool of terrestrial carbon. Therefore, the objective of the study was to investigate the effect of climate on the radiocarbon Mean Resistance Time (MRT) in surface and subsurface soils in some of rangelands of Khuzestan Province, Iran. This way, rangelands were selected under different climates in two regions called Izeh and Ramhormoz. In both regions, the control profiles were studied to determine physical and chemical properties of the soil, carbon forms and 14C (carbon-14 isotopic ratio). The results showed that the MRT of the corresponding depths of Ramhormoz profile (with lower mean annual rainfall) was far higher than those of the Izeh profile, due to higher turnover of fresh organic matters in Izeh rangeland. Unlike Izeh profile, the MRT in Ramhormoz profile did not increase with depth owing to clay content and topographic position of the region i.e. being a depositional site. Overall, the age of carbon-14 in the top horizons of the study areas was mostly affected by factors such as climate, land management and the presence of decomposition sensitive forms of carbon. While, in deep soil the age of carbon was affected by other factors, especially soil taxa, clay content, topographic position (erosional or depositional sites) and discontinuity in soil parameters such as bulk density than by climate.